Key challenges for implementing a Canadian-based objective structured clinical examination (OSCE) in a Middle Eastern context (Canadian Medical Education Journal, 2016)
Globalization of medical education is occurring at a rapid pace and many regions of the world are adapting curricula, teaching methods, and assessment tools from established programs. In the Middle East, the use of Objective Structured Clinical Examinations (OSCEs) is rare. The College of Pharmacy at Qatar University recently partnered with the University of Toronto and the Supreme Council of Health in Qatar to adapt policies and procedures of a Canadian-based OSCE as an exit-from-degree assessment for pharmacy students in Qatar. Despite many cultural and contextual barriers, the OSCE was implemented successfully and is now an integrated component of the pharmacy curriculum. This paper aims to provide insight into the adoption and implementation process by identifying four major cultural and contextual challenges associated with OSCEs: assessment tools, standardized actors, assessor calibration, and standard setting. Proposed solutions to the challenges are also given. Findings are relevant to international programs attempting to adapt OSCEs into their contexts, as well as Canadian programs facing increasing rates of cultural diversity within student and assessor populations.